2014
DOI: 10.1002/ajim.22339
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of workers' compensation costs due to falls from height among union carpenters, Washington State

Abstract: Significant progress has been made in reducing WC payments associated with FFH in this cohort particularly through 1996; primary gains reflect reduction in frequency of falls. FFH that occur remain costly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…To conclude, a critical review has been undertaken to summarise the existing FFH literature, highlight the inadequacies and provide future research directions. The reviewed FFH literature was mainly drawn from peer-reviewed journal articles and conference proceedings [ 3 , 4 , 5 , 6 , 7 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ,…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, a critical review has been undertaken to summarise the existing FFH literature, highlight the inadequacies and provide future research directions. The reviewed FFH literature was mainly drawn from peer-reviewed journal articles and conference proceedings [ 3 , 4 , 5 , 6 , 7 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ,…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort was limited to individuals who worked at least 3 months of union hours, with observation beginning in the month eligibility criteria were met (i.e., the 3rd month of union work). As in prior research with these data (e.g., [Lipscomb et al, ]), carpenters were assigned a predominant type of work based on the work most commonly performed by the union local to which they belong: residential building, light/heavy/mixed commercial, drywall installation, millwrighting, and piledriving. Some carpenters were affiliated with a union local outside of WA State for which information on the predominant type of work was not available.…”
Section: Methodsmentioning
confidence: 99%
“…Lipscomb et al. (2014) investigated fall‐related compensation costs and age factors and found that mean costs were 2.3 times greater among carpenters aged over 50 than those aged under 30.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Camino López, González Alcantara, Fontaneda, and Mañanes (2018) investigated the relationship between the age of injured workers, days off due to injury, and accident severity to determine the implications of accumulated fatigue during the working day and throughout the week. Lipscomb et al (2014) investigated fall-related compensation costs and age factors and found that mean costs were 2.3 times greater among carpenters aged over 50 than those aged under 30.…”
Section: Safety Risk Incidents In Construction Projectsmentioning
confidence: 99%